2012
DOI: 10.3109/09638288.2012.680650
|View full text |Cite
|
Sign up to set email alerts
|

Contextual influences of parenting behaviors for children with neurodevelopmental disorders: results from a Canadian national survey

Abstract: Other Child, parent, and social context factors are associated with parenting behaviors but these associations vary by the child's health group. Parenting behaviors differ for children with NDDs with and without EBPs. These findings offer important implications for practice and research and point to the importance of considering multiple contexts of influence, as well as their interactions, in understanding differences in parenting behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 62 publications
4
38
2
4
Order By: Relevance
“…Parents of boys reported equivalent nurturance regardless of the ability status of the child. Taken together, these findings build on work that suggests that parenting strategies and family functioning may differ in families with a child with an NDC from families with TD children (e.g., Arim et al, 2012;Blum et al, 1991;Britner, Morog, Pianta, & Marvin, 2003) by suggest ing that girls with NDCs may not have as much access to nurturing parenting practices. At least in childhood, such prac tices may benefit girls by creating a warmer and more sensitive caregiving environment.…”
Section: Discussionmentioning
confidence: 67%
“…Parents of boys reported equivalent nurturance regardless of the ability status of the child. Taken together, these findings build on work that suggests that parenting strategies and family functioning may differ in families with a child with an NDC from families with TD children (e.g., Arim et al, 2012;Blum et al, 1991;Britner, Morog, Pianta, & Marvin, 2003) by suggest ing that girls with NDCs may not have as much access to nurturing parenting practices. At least in childhood, such prac tices may benefit girls by creating a warmer and more sensitive caregiving environment.…”
Section: Discussionmentioning
confidence: 67%
“…Tačiau jau bene šim-tmetį besitęsiančios diskusijos dėl gimimo eiliškumo reikšmės asmens psichologinėms savybėms labiausiai siejamos su Adlerio vardu. Adleris teigė, kad, vertinant žmogų, svarbu žinoti aplinkybes, kuriomis jis augo, ypač tai, kokią padėtį jis ar ji užėmė tarp brolių ir seserų, jei jų turėjo (Adler, 1958;Ansbacher & Ansbacher, 1964). Kad ir kelintas šeimoje būtų gimęs vaikas, sunkiausių padarinių turi jo noras siekti pranašumo prieš kitus vaikus; vaiko aplinkybės ypač pasikeičia patyrus vadinamąjį "nuvertimą nuo sosto" gimus kitam vaikui (Adler, 1958).…”
Section: įVadasunclassified
“…Dėl šių priežas-čių, vartojant didžiojo penketo asmenybės apibūdinimo terminus, pirmagimiai yra daugiau pasiekiantys ir sąmoningesni, o antrieji vaikai -maištingesni ir atviresni naujoms patirtims (Sulloway, 1996). Lietuvoje panašiu metu gimimo eiliškumu -kaip individualios raidos veiksniu -domėjosi Bagdonas, Greblikienė ir Kaniavienė (1996). Jų atliktų tyrimų rezultatai ir aštuntojo XX amžiaus dešimtmečio psichologinių tyrimų apžval-ga rodo, kad pirmagimiams ne tik būdingi didesni intelekto (ypač kalbinių gebėjimų) įverčiai, bet ir kiek didesnis internalumas, rodantis mažesnį priklausomumą nuo aplinkinių ar kitų mažai kontroliuojamų veiksnių (Bagdonas ir kt., 1996).…”
Section: įVadasunclassified
See 1 more Smart Citation
“…Research has shown that perceived parental support predicted higher global self-worth and social competence, and fewer externalizing behavior problems in children [44], whereas harsh parenting was associated with difficulties in emotion regulation skills, and both higher internalizing and externalizing behavior problems. Our previous research has shown that parents of children with both NDDs and externalizing behaviour problems (EBPs) reported less consistency and more ineffective parenting behaviors as compared to parents of children with neither health conditions, even after controlling for child, parent and family socio-demographic characteristics [45], as well as other factors including family and social context [46]. In contrast, although parents of children with NDDs reported less positive interactions with their child compared to parents of children with neither NDDs nor EBPs, this difference disappeared after controlling for socio-demographic characteristics, parental health and social context factors, such as family functioning and social support [46].…”
Section: Introductionmentioning
confidence: 99%